RAPID DETECTION OF ?-THALASSEMIA MUTATIONS IN THAILAND USING MULTIPLEX ARMS - D. Shimbhu; S. Mirasena; M. Sanguansermsri; T. Sanguansermsri (ASEAN Journal on Science and Technology for Development, 2008)
The number of mutations underlining b-thalassemia generate a wide variety of different clinical phenotypes. An understanding of the genotype is important for medical personnel in order to provide proper counseling to patients and their families. Characterization of these mutations should aid the planning of a prenatal diagnosis program for bthalassemia. The heterogeneity of the mutations makes it difficult and time consuming to identify the mutation in some individuals. We developed a single-tube multiplex amplification refractory mutation system (multiplex ARMS) to identify common ethnic- specific b-thalassemia mutations. Confirmation of multiplex ARMS results was carried out using direct sequencing. Three thousand three hundred twenty two people from Phitsanulok province were screened for the b-thalassemia trait by quantitation of HbA2 with microcolumn chromatography and the genotypes of mutations were characterized using multiplex ARMS and direct sequencing. We found that the deletion at codons 41/42 (-TCTT) was the most frequent (48%), codon 17 (A®T) (30%), -28 (A®G) (6%) and IVS-I-1(G®T) (6%) were the second and third in frequency respectively. A -87 (C®A) mutation (4%), IVS II-654 (C®T) (2%), codons 71/72 (+A) (2%) and codon 35 (C®A) mutations (2%) were also found. These techniques were found to be a valuable tool for analysis of b-thalassemia mutations because they are accurate, simple, and speedy in operation. The application for the diagnosis of severe thalassemia in high-risk pregnancies is promising.